MORPHO SEMANTICS, NOUN ANALYZATION OF MORPHEMES WITH SUFFIXES *FUL AND *LESS. (Лучшие интеллектуальные исследования, 2025)
Abstract: These days, there is a great deal of discussion on the morphosemantic purpose of suffixes like as "full" and "less," amongst others. However, it appears that in order to get more knowledge about them, we need to address the qualities of the nouns with which they are related in order to talk about the features of the nouns.